Soil Erosion Rainfall Erosivity and Risk Assessment - Hrissanthou, Vlassios; Kaffas, Konstantinos (IntechOpen, 2019)
In the first section of this book on soil erosion, an introduction to the soil erosion problem is presented. In the first part of the second section, rainfall erosivity is estimated on the basis of pluviograph records and cumulative rainfall depths by means of empirical equations and machine learning methods. In the second part of the second section, a physically-based, hydrodynamic, finite element model is described for the computation of surface runoff and channel flows. In the first part of the third section, the soil erosion risk is assessed in two different basins. In the second part of the third section, the soil erosion risk management in a basin is evaluated, and the delimitation of the areas requiring priority planning is achieved.